Efektivitas Penggunaan Birthball Untuk Mengurangi Intensitas Nyeri Persalinan Kala I - Siti Farida; Sri Wahyuningsih Nugraheni (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Visceral pain experienced by women in labor in the first stage of labor is caused by cervical changes and uterine ischemia. In the first stage of the latent phase, cervical effacement occurs, while in the first stage of active and transitional phases, cervical dilatation occurs and the lowest area of ​​the fetus descends. Birthball (birth ball) is a physical therapy or simple exercise using a ball which, if performed on first-stage inpartum mothers, can help progress in labor and reduce pain. The purpose of this study was to determine the effectiveness of the use of birthballs in reducing the intensity of labor pain in the first stage. This type of research was a quasi-experimental design with a pretest-posttest group design, namely by comparing 1 group with 2 treatments, namely pretest and posttest in the form of measuring effectiveness before and after use. birthball on the intensity of labor pain in the first stage in the group. The sample in this study was the first stage of physiological maternity women who met the inclusion criteria as many as 28 people. The results of statistical tests obtained a p value of 0.00 so it can be concluded that there is a significant difference in the intensity of labor pain in the first stage before and after the use of a birthball with an average value of the intensity of labor pain in the first stage before the use of a birthball, which is 5.54 and after the use of a birthball. of 3.32